ANALISIS BAURAN PEMASARAN 4P’s PADA KEPUTUSANDAN KEPUASAN PEMBELIAN TERHADAP MINATBELI ULANG DAN LOYALITAS PELANGGANSTUDI KASUS PADA UKM KULINER WARDOM PAK ATO - Dhani, Rabiah Rahma; Sumitro, Sumitro; Efendi Siregar, Zulkifli Musannif (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine and analyze the effect of 4p's marketing mix on purchasing decisions and satisfaction and its impact on repurchase interest and customer loyalty in the case study of Wardom Pak Ato's Culinary UKM. The population in this study are consumers who buy at Warung Indomie Pak Ato located in Ujuang Bandar, Kec. Rantau Selatan. This research used a research instrument in the form of a questionnaire with a total sample of 100 respondents. Sampling in this study using accidental sampling (Accidental Sampling) which is part of sampling non-probability (Non-Probability Sampling). The feasibility test of the research instrument as well as descriptive analysis of the characteristics of the respondents used version 22 of the softwareSPSS (Statistical Package for the Social Science). While the data analysis technique used the path analysis model with the help of software SmartPLS version 3.0.